Novel modification of anhydrous transition metal oxalates from powder diffraction. Issue 11 (13th October 2017) - Puzan, Anna N.; Baumer, Vyacheslav N.; Mateychenko, Pavel V.
Abstract : The crystal structures of the novel γ‐modification of anhydrous oxalates have been determined from powder diffraction data for MnC2 O4 and CdC2 O4 obtained during thermal decomposition of the corresponding hydrates. The distinctive features of this modification are loose packing and low densities compared with the known α‐ and β‐modifications of anhydrous transition metal oxalates. Abstract : The known metal–C2 O4 structures may be divided into two modifications, α and β. The α‐modification has an order–disorder struxture, revealing one‐dimensional disordering of the metal–oxalate chains, and the β‐modification is ordered. The crystal structures of orthorhombic γ‐MnC2 O4 {poly[μ‐oxalato‐manganese(II)]; space group Pmna, a = 7.1333 (1), b = 5.8787 (1), c = 9.0186 (2) Å, V = 378.19 (1) Å 3, Z = 4 and Dx = 2.511 Mg m −3 } and γ‐CdC2 O4 {poly[μ‐oxalato‐cadmium(II)]; space group Pmna, a = 7.3218 (1), b = 6.0231 (1), c = 9.2546 (2) Å, V = 408.13 (1) Å 3, Z = 4 and Dx = 3.262 Mg m −3 } have been obtained from powder diffraction patterns. The structures are isostructural. Each metal atom in each structure is coordinated by seven O atoms which belong to five oxalate ions. The crystal packing, which contains noticeable cavities in the [101] and [001] directions, is not close packed and essentially differs from the known disordered α‐ and ordered β‐modifications of transition metal oxalates. This modification seems to be metastable. It was found that a spontaneous γ→β phase transition takes place for γ‐CdC2 O4 .